LINGUISTIC PORTRAYAL OF GASLIGHTING IN INTERPERSONAL RELATIONSHIPS: - Ghaltakhchyan, Siranoush (Armenian Folia Anglistika, 2024)
The paper explores the intricate interplay between language and manipulation, focusing on the linguistic and extralinguistic manifestations of gaslighting in interpersonal communication. Gaslighting is viewed as a form of manipulative communication that involves deliberate denial or distortion of reality, making the victims doubt their own actions, perception, memory and sanity. The victim’s ongoing confusion leads to a sense of powerlessness and a diminished self-esteem. Using a qualitative-quantitative linguistic method, the paper dissects the portrayal of gaslighting dynamics in the short psychological film Your Reality, which is based on real-life experiences. Through comprehensive psycholinguistic analysis, an attempt is made to illustrate how specific manipulative tactics are intentionally employed to achieve gaslighter’s abusive objectives. Examining the subtle, yet powerful verbal and non-verbal manipulative tactics employed in the film, the research aims to elucidate gaslighting dynamics in interpersonal communication and empower readers with valuable insights into recognizing and addressing early signs of such deceitful behavior in real-life situation. Thus, this knowledge is crucial for fostering awareness, establishing boundaries to prevent gaslighting attempts and promoting healthy communication.